Branded content for VOD catalogs promotion: La Tarotista, a talk show of Netflix for YouTube - Moreno Albarracín, Belén (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Netflix tries to attract the public with promotional actions which go beyond conventional advertising. The company opts for branded content, through strategies based on its own catalog. The objective of this research is studying how Netflix promotes itself through a previously unused format, the talk show La Tarotista, produced for YouTube. After a content analysis, a tendency towards the transmission of organizational identity through the aesthetic-visual code is observed, focusing the discourse on the life stories of the guest cast. Thus, Netflix humanizes its catalog, giving as much relevance to fiction as to the context in which it takes place.